2007
DOI: 10.1016/j.otohns.2006.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Type III cartilage “shield” tympanoplasty: An effective procedure for hearing improvement

Abstract: Type III cartilage "shield" tympanoplasty is an effective technique for hearing improvement in selected patients with chronic otitis media. The results of this procedure are similar to those obtained with partial ossicular replacement prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
5
24
0
Order By: Relevance
“…They also reported no cases of extrusion. In 2007, Kyrodimos et al [8] presented their experience of the so-called "type III cartilage shield tympanoplasty, " which consisted of repairing large tympanic membrane perforation and ossicular discontinuity with one piece of full thickness conchal cartilage shaped as a shield. They used the cartilage shield to replace the entire tympanic membrane and reconstructed sound transmission by placing the cartilage on the head of the stapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported no cases of extrusion. In 2007, Kyrodimos et al [8] presented their experience of the so-called "type III cartilage shield tympanoplasty, " which consisted of repairing large tympanic membrane perforation and ossicular discontinuity with one piece of full thickness conchal cartilage shaped as a shield. They used the cartilage shield to replace the entire tympanic membrane and reconstructed sound transmission by placing the cartilage on the head of the stapes.…”
Section: Discussionmentioning
confidence: 99%
“…In an exclusive large pediatric cohort, Nevoux et al [10] reported the results of the cartilage shield tympanoplasty technique. Unlike Kyrodimos et al [8] , Nevoux et al [10] interposed two additional pieces of cartilage between the stapes capitulum. At 1 year, closure of the ABG to within 20 dB was achieved in 62.2% of the cases, which is an interesting result in children taking into account the frequent onset of otitis media with effusion in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Small defects that remain after reconstruction with a cartilage piece are filled up by bits of temporalis muscle or smashed cartilage. 4 Temporalis fascia kept lateral to the piece of cartilage and also to cover any defects in tympanic membrane by underlay method. Adequate gelfoam kept in mesotympanum, mastoid and also in the ear canal.…”
Section: Methodsmentioning
confidence: 99%
“…In 4 patients, the long process of Incus was partially eroded and a small piece of cartilage was used to bridge the gap between stapes head and remaining of Incus. In 2 of the patients, only stapes was present where a type III cartilage shield tympanoplasty [4] was carried out. In 4 patients, all ossicles were absent and no ossiculoplasty was performed in them.…”
Section: Methodsmentioning
confidence: 99%